Nuances of preoperative care before cataract extraction. What do we overlook when performing biometry, calculating IOL power, and examining the eye? - A.B. Movsisyan; A.E. Egorov (РМЖ "Клиническая офтальмология")
A.B. Movsisyan1,2, A.E. Egorov1,2 1Hospital for War Veterans № 2, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Modern cataract surgery is increasingly regarded as a refractive procedure. The focus has shifted from practicing and refining surgical steps towards personalized intraocular lens (IOL) choice based on the eye parameters of each individual. The best possible refractive outcome is now the priority. All components of biometry contribute to IOL power calculation accuracy. Therefore, any errors, a method of evaluating each parameter, and a technician’s experience are important. In addition, refraction, macular disorders, and prior surgical procedures affect IOL choice, preoperative care, and the extent of surgery. Moreover, subsequent changes in the IOL position that results in refractive errors after cataract surgery (this depends on the formula for IOL power calculation) should also be considered. The accuracy of IOL power calculation is affected by the inaccuracy of current biometry techniques and postoperative changes of the globe. Personalization of theoretical formula s provides better accuracy of IOL power calculations to meet modern trends in intraocular correction. Supplements containing macular pigments prevent macular degeneration and protect the macular zone. Keywords: cataract, refraction, cataract surgery, biometry, IOL power calculation, IOL power calculation formulas, retina, age-related macular degeneration. For citation: Movsisyan A.B., Egorov A.E. Nuances of preoperative care before cataract extraction. What do we overlook when performing biometry, calculating IOL power, and examining the eye? Russian Journal of Clinical Ophthalmology. 2021;21(3):159–163 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-159-163.